1997
DOI: 10.1083/jcb.139.1.129
|View full text |Cite
|
Sign up to set email alerts
|

Desmin Is Essential for the Tensile Strength and Integrity of Myofibrils but Not for Myogenic Commitment, Differentiation, and Fusion of Skeletal Muscle

Abstract: A null mutation was introduced into the mouse desmin gene by homologous recombination. The desmin knockout mice (Des −/−) develop normally and are fertile. However, defects were observed after birth in skeletal, smooth, and cardiac muscles (Li, Z., E. Colucci-Guyon, M. Pincon-Raymond, M. Mericskay, S. Pournin, D. Paulin, and C. Babinet. 1996. Dev. Biol. 175:362–366; Milner, D.J., G. Weitzer, D. Tran, A. Bradley, and Y. Capetanaki. 1996. J. Cell Biol. 134:1255– 1270). In the present study we have carried out a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
292
4
9

Year Published

1999
1999
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(320 citation statements)
references
References 65 publications
(57 reference statements)
15
292
4
9
Order By: Relevance
“…In that study, the extensor digitorum longus (EDL) had an immediate loss of desmin, and it was only after 15 min of repeated contractions that the TA showed a significant loss in desmin, indicating that anatomical and biomechanical variables are likely important. Like muscles in dystrophin-knockout mice, muscles in desmin-knockout mice are reported to be more vulnerable to eccentric injury (29), although a different study indicates that muscles in desmin-knockout mice are much less vulnerable to injury than controls (44). Such disparate findings illustrate the present lack of full understanding we have for these various cytoskeletal proteins.…”
Section: Discussioncontrasting
confidence: 46%
“…In that study, the extensor digitorum longus (EDL) had an immediate loss of desmin, and it was only after 15 min of repeated contractions that the TA showed a significant loss in desmin, indicating that anatomical and biomechanical variables are likely important. Like muscles in dystrophin-knockout mice, muscles in desmin-knockout mice are reported to be more vulnerable to eccentric injury (29), although a different study indicates that muscles in desmin-knockout mice are much less vulnerable to injury than controls (44). Such disparate findings illustrate the present lack of full understanding we have for these various cytoskeletal proteins.…”
Section: Discussioncontrasting
confidence: 46%
“…Desmin and creatine kinase have been attributed functional roles in mature myocytes and are highly expressed in muscle (Shainberg et al, 1971;Li et al, 1997). Desmin expression in proliferating myoblasts is governed by a 5 0 proximal promoter region (myoblastspecific region), and its elevated expression during differentiation is governed by a 5 0 distal enhancer (myotube-specific region) that contains an E-box commonly found in muscle-specific genes (Wentworth et al, 1991;Li and Paulin, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Knock-out of the desmin gene demonstrated its signi¢cant roles in cardiac, skeletal and smooth muscle function [5,17,18]. Here we reported that desmin v1À48 lacking 48 amino acids of the amino-terminal head domain a¡ects cardiac, skeletal and smooth muscle to di¡erent degrees in EBs thus demonstrating that desmin exerts di¡erent roles via its head domain during muscle development.…”
Section: Discussionmentioning
confidence: 81%